Jogo de cena e o dispositivo fílmico de Eduardo Coutinho como construção de uma ética documental - Rosa, Igor Miguel da Silveira (2019)
The aim of this research is to understand how the device of Playing (2007) is formed from devices used in others documentaries of Eduardo Coutinho, and how this device is created to cope with an ethical demand of relations between documentarist, documented, theme and viewer. For this purpose, a device conceptualization in the study of the documentary is needed to understand when the concept of device and the modifications of the term by different authors appear, in order to arrive at the definition as rules of the game. The research starts studying the ethical demands for documentary history in order to understand how, at each time, driven by its own ethical issues, the documentary took on different forms. It is sought to understand how ethical relations and devices appear in the director's documentary filmography to elaborate how those elements are constructed in each film and how they appear in Playing (2007) and what this documentary differs from others of the director's career.